Book Publishing in Lithuania (1940–1941) - Butkus, Tadas (Knygotyra, 1973)
In 1940 after the overthrow of fascism and reestalishment of the Soviet Power in Lithuania, besides many socialist reforms in the spheres of economics and culture, book publishing was also reorganized.The Government’s decision of Sept 27, 1940, nationalization of all publishing houses was declared. Instead of small private publishing firms belonging to different organizations, large-scale State Publishing House of Lithuanian S.S.R. was established Its task was 10 provide the people with all kinds of books. Besides, the Stale Publishing House was dealing in book sale, as all the nationalized bookshops had been transferred to the House.The newly established Publishing House encountered many administrative difficulties. There was but poor experience of state-scale book−publishing, a lack of editorial specialists (no institutions of editorial experts existed in bourgeois Lithuania). In 1940 the State Publishing House, however, managed in publishing 68 books (1.2 million copies). The total of books publishing in 1940–1941 (till the war started) was 216 (3.1 million copies).It should be noted that in 1940–1941 the State Publishing House was not the only firm to publish books. Books were also published by many individual offices and organizations. Thus the total during 1940–1941 (till the war started) makes 1067 books (about 8 million copies).The World War II interrupted the work of the State Publishing House which was evacuated to Moscow and continued its activities from 1942.